A new perspective on PTSD symptoms after traumatic vs stressful life events and the role of gender. Issue 1 (1st January 2017) - van den Berg, Lisa J. M.; Tollenaar, Marieke S.; Spinhoven, Philip; Penninx, Brenda W. J. H.; Elzinga, Bernet M.
ABSTRACT: Background : There is an ongoing debate about the validity of the A1 criterion of PTSD. Whereas the DSM-5 has opted for a more stringent A1 criterion, the ICD-11 will leave it out as a key criterion. Objective : Here we investigated whether formal DSM-IV-TR traumatic (A1) and stressful (non-A1) events differ with regard to PTSD symptom profiles, and whether there is a gender difference in this respect. Method : This was examined in a large, mostly clinical sample from the Netherlands Study of Depression and Anxiety ( n  = 1433). Participants described their most bothersome (index) event and were assigned to either an A1 or non-A1 event group according to this index event. Results : Remarkably, in men PTSD symptoms were even more severe after non-A1 than A1 events, whereas in women symptoms were equally severe after non-A1 and A1 events. Moreover, while women showed significantly higher PTSD symptoms after A1 events than men (29.9 versus 15.4% met PTSD criteria), there was no gender difference after non-A1 events (women: 28.2%; men: 31.3%). Furthermore, anxiety and perceived impact were higher in women than men, which was associated with PTSD symptom severity. Conclusion : In sum, while women showed similar levels of PTSD symptoms after both event types, men reported even higher levels of PTSD symptoms after non-A1 than A1 events. These findings shed a new light on the role of gender in PTSD symptomatology and the clinical usefulness of the A1 criterion.